2013
DOI: 10.1038/ismej.2013.217
|View full text |Cite
|
Sign up to set email alerts
|

Microbial population and functional dynamics associated with surface potential and carbon metabolism

Abstract: Microbial extracellular electron transfer (EET) to solid surfaces is an important reaction for metal reduction occurring in various anoxic environments. However, it is challenging to accurately characterize EET-active microbial communities and each member's contribution to EET reactions because of changes in composition and concentrations of electron donors and solid-phase acceptors. Here, we used bioelectrochemical systems to systematically evaluate the synergistic effects of carbon source and surface redox p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(134 citation statements)
references
References 54 publications
4
124
2
Order By: Relevance
“…However a recent study demonstrated that different Geobacter clades and different microbial associations were linked to specific potentials. In fact, Geobacter metallireducens clade appeared to be associated with more negative potentials, while Geobacter clades 1 and 2 were observed at more positive potentials [34]. The effect of the electrode potential on the cathodic communities is not well described.…”
Section: Microbial Community Characterizationmentioning
confidence: 89%
“…However a recent study demonstrated that different Geobacter clades and different microbial associations were linked to specific potentials. In fact, Geobacter metallireducens clade appeared to be associated with more negative potentials, while Geobacter clades 1 and 2 were observed at more positive potentials [34]. The effect of the electrode potential on the cathodic communities is not well described.…”
Section: Microbial Community Characterizationmentioning
confidence: 89%
“…The biofilm acts as a catalyst for the metabolism of unrefined substrates (organic matter), during which electrons, protons, and other organic compounds are released. An understanding of the anodic reaction mechanism, together with an improvement of the electron transfer and the biofilm growth needs to be addressed to achieve an increased power density [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies were carried out to expand the application of BESs and increase the efficiency of electricity production (9)(10)(11). One strategy is to understand and steer the microbial community on electrode surfaces (12). We are far from understanding the role of individual groups of microorganisms that thrive on anode surfaces in nonaxenic systems.…”
mentioning
confidence: 99%